2023
DOI: 10.1039/d3nj00754e
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of N, B-doped carbon dots and their multifunctional applications in the detection of tin ions and gallic acid and information encryption

Abstract: In this study, simple and rapid preparation of multi-functional carbon dots, which are employed for the detection of tin ions and GA and information encryption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The external heavy atom effect (EHE) is a commonly used method to enhance the performance of RTP luminous materials. 20–25 It promotes intersystem crossing (ISC) rates and enhances spin–orbit coupling (SOC) by specific intermolecular interactions between the external heavy atom and luminous body. EHE is considered a simpler and more convenient strategy for achieving tuneable RTP.…”
Section: Introductionmentioning
confidence: 99%
“…The external heavy atom effect (EHE) is a commonly used method to enhance the performance of RTP luminous materials. 20–25 It promotes intersystem crossing (ISC) rates and enhances spin–orbit coupling (SOC) by specific intermolecular interactions between the external heavy atom and luminous body. EHE is considered a simpler and more convenient strategy for achieving tuneable RTP.…”
Section: Introductionmentioning
confidence: 99%
“…33 This finding indicates that the boron dopant may lead to double emission in C-dots, which is a very useful property for high-level anticounterfeiting applications. 34 As the structure of C-dots is complicated, it is very difficult to explain well the PL origin of the C-dots, especially for the type of C-dots having multiple emissions. Meanwhile, it is highly desirable to understand deeply the exciton dynamics in C-dots on the picosecond time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh et al reported red-emitting C-dots, and they found a newly formed additional excited-state level as boron doping leads to a significant amount of the excited-state population compared to undoped C-dots . This finding indicates that the boron dopant may lead to double emission in C-dots, which is a very useful property for high-level anticounterfeiting applications . As the structure of C-dots is complicated, it is very difficult to explain well the PL origin of the C-dots, especially for the type of C-dots having multiple emissions.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 A significant emphasis has been placed on modifying their chemical structures through the introduction of heteroatomic impurities such as boron, nitrogen, oxygen, and sulfur. 12–16 These impurities generate intragap states in CDs, which alter their electronic band structures and shift their PL wavelengths. 17–19 Among these impurities, nitrogen is considered the optimal dopant for CDs due to its similar atomic size to carbon 20,21 and its ability to form strong covalent bonds with carbon.…”
Section: Introductionmentioning
confidence: 99%